Statistical analyses of potential evapotranspiration changes over theperiod 1930–2012 in the Nile River riparian countries - Onyutha, Charles (Agricultural and Forest Meteorology, 2016)
Changes in potential evapotranspiration (PET) in the Nile Basin tend to be analyzed mostly based onshort-term remotely sensed annual data. In this study, long-term country-wide series from 1930 to 2012were used to assess changes in annual and seasonal PET in all the Nile River Riparian Countries (NRRCs).Variability was investigated using the nonparametric anomaly indicator method. Trend was assessed bothgraphically and statistically using the cumulative rank difference method. The PET totals from 1930s to1970s (from around 1980 to early 2000s) were generally below (above) the mean of the long-term data.Moreover, for this period from around 1980 to early 2000s, both annual and seasonal PET totals in most ofthe NRRCs were characterized by an increase significant at 5% level. This increase in the PET influenced thelong-term trend based on the full time series from 1930 to 2012 towards positive direction. For instance,the long-term annual PET exhibited increasing trend significant at 5% level in 2 of the 6 countries in theequatorial region. However, the positive trends in the PET of Sudan, Ethiopia, Eritrea and Egypt wereinsignificant at 5% level. It was found that the temporal changes in PET especially during rainy seasonscan be explained at the significance level of 5% by the rainfall variation. Sampling uncertainties on the PETtrend magnitudes are quantified and provided. The findings in this study are important for determiningthe crop water requirements especially in arid conditions where rainfall is unreliable and low in volume.
Keywords: CRD Test; Trend Analyses; NAIM; Variability Analyses; Nile River; Evapotranspirationa